Numerical Analysis of Integral Characteristics for the Condenser Setups of Independent Power-Supply Sources with the Closed-Looped Thermodynamic Cycle; Mathematical Problems in Engineering; Vol. 2015, article ID 535747 - Vysokomornaya O. V. Olga Valeryevna (2015, 2015)
Title screen